Genetic effects of BDKRB2 and KNG1 on deep venous thrombosis after orthopedic surgery and the potential mediator. Issue 1 (December 2018) - Wang, Qingfeng; Cheng, Guoping; Wang, Xiaohui; Wang, Dandan; Yang, Yanmei; Chen, Ke; Ye, Jiumin; Qing, Zhong
Abstract Deep venous thrombosis (DVT) is a common complication of orthopedic surgery. Genetic risk factors and high heritability carried a substantial risk of DVT. In this study, we aimed to investigate the potential association in the Han Chinese population between the polymorphisms ofBDKRB2 andKNG1 and DVT after orthopedic surgery (DVTAOS). A total of 3, 010 study subjects comprising 892 DVT cases and 2, 118 controls were included in the study, and 39 single nucleotide polymorphisms (SNPs) in total (30 forBDKRB2 and 9 forKNG1 ) were chosen for genotyping. Two SNPs, rs710446 (OR = 1.27, P  = 0.00016) and rs2069588 (OR = 1.29, P  = 0.00056), were identified as significantly associated with DVTAOS. After adjusting for BMI, the significance of rs2069588 decreased (P  = 0.0013). Haplotype analyses showed that an LD block containing rs2069588 significantly correlated with the DVTAOS risk. Moreover, bioinformatics analysis indicated that hsa-miR-758-5p andBDKRB2 formed miRNA/SNP target duplexes if the rs2069588 allele was in the T form, suggesting that rs2069588 may alterBDKRB2 expression by affecting hsa-miR-758-5p/single-nucleotide polymorphism target duplexes. Our results demonstrate additional evidence supporting that there is an important role for theKNG1 andBDKRB2 genes in the increased susceptibility of DVTAOS.